Indexing out of poverty? Fiscal drag and benefit erosion in cross-national perspective - Alari Paulus; Holly Sutherland; Iva Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2019)
We assess how tax-benefit policy developments in 2001-2011 affected the household income distribution in seven EU countries. We use the standard microsimulation-based decomposition method, separating further the effect of structural policy changes and the uprating of monetary parameters, which allows us to measure the extent of fiscal drag and benefit erosion in practice. The results show that despite different fiscal effects, policies overall mostly reduced poverty and inequality and both types of policy developments had sizeable effects on the income distribution. We also find that the uprating of monetary parameters not only had a positive effect on household incomes, meaning fiscal drag and benefit erosion were avoided, but generally also contributed more to poverty and inequality reduction than structural policy reforms.
Keywords: D31; H23; I32; 330; income distribution; tax-benefit policies; decomposition; microsimulation